NIAT MEMBELI GREEN PRODUCT PADA GENERASI MILLENIAL DI INDONESIA - Ikhsan, Muhammad; Salim, Muhartini; Hayu, Rina Suthia (Universitas Prof. Dr. Hazairin SH, 2023)
This study focuses on millennials' intentions to buy green products in Indonesia. The Theory of Planned Behavior (TPB) was applied in this study. The purpose of this study is to investigate the impact of environmental awareness, environmental knowledge, attitudes, behavioral control perceptions, and subjective norms on purchase intent. The quantitative research approach was applied, and primary data were gathered using an online questionnaire. This research included 230 respondents who planned to buy ecologically friendly items. The analysis approach used in this work is Structural Equation Modeling (SEM). AMOS 20.0 for Windows was utilized as the testing software. The data reveal that the higher the level of environmental concern, attitude, and perceived behavioral control, the greater the desire to buy green items among Indonesian millennials. While there is a negative relationship between environmental knowledge characteristics and subjective standards and the propensity to buy green items. Practical advice in this study is that it is hoped that providers of environmentally friendly products (green products) can provide a more detailed explanation of the benefits of green products to the millennial generation in order to create an attitude of care for the environment and provide information that environmentally friendly products are easily obtained in order to encourage consumers to have the intention to buy environmentally friendly products.